1998
DOI: 10.1046/j.1360-0443.1998.939141712.x
|View full text |Cite
|
Sign up to set email alerts
|

High rates of drug use, but low rates of HIV risk behaviours among injecting drug users during incarceration in Dutch prisons

Abstract: Contrary to findings from other countries, low levels of HIV risk behaviours occur among imprisoned drug injectors in The Netherlands. Intra-prison HIV preventive measures should be considered taking into account the nationally, regionally or locally varying conditions within the existing prisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Despite the sensitivities regarding same-gender practice, on average, 2.5% of prisoners, with no difference between injecting and non-injecting drug users, reported having had sex with another man in this prison. While low rates of same-gender sexual practices have been reported among prisoners in some European countries, 26,27 other studies have reported higher proportions (over 10%) of male prisoners engaging in same-gender sex while in prison. 28,29 Importantly, the finding that none of those who had had same-gender sex in this prison used a condom for their last sex encounter is worrying and deserves careful consideration by the prison health policy makers.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the sensitivities regarding same-gender practice, on average, 2.5% of prisoners, with no difference between injecting and non-injecting drug users, reported having had sex with another man in this prison. While low rates of same-gender sexual practices have been reported among prisoners in some European countries, 26,27 other studies have reported higher proportions (over 10%) of male prisoners engaging in same-gender sex while in prison. 28,29 Importantly, the finding that none of those who had had same-gender sex in this prison used a condom for their last sex encounter is worrying and deserves careful consideration by the prison health policy makers.…”
Section: Discussionmentioning
confidence: 98%
“…However retrospective studies that involve describing the salient events related to incarceration have been used previously (Buavirat et al, 2003; van Haastrecht et al, 1998) and a high consistency of responses related to self-reported drug use has been documented (Darke, 1998; Shillington et al, 1995). Further, we asked numerous questions related to the context of the relapse episode, which may have helped with recall (Means et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One of these individuals did seroconvert to HCV, an event which occurred more than 18 months after 13 being released. Besides the documented risk associated with injection drug use while in prison, heightened vulnerability may play an important role in increasing high-risk injection behaviours and HCV acquisition after release (37).…”
Section: Resultsmentioning
confidence: 99%